Biomarker responses of Eisenia andrei to a polymetallic gradient near a lead mining site in North Tunisia. (November 2016) - Boughattas, Iteb; Hattab, Sabrine; Boussetta, Hamadi; Sappin-Didier, Valérie; Viarengo, Aldo; Banni, Mohamed; Sforzini, Susanna
Abstract: Eisenia andrei earthworms were exposed for 7 and 14 days to six samples of soil taken from around an abandoned lead (Pb) mine and characterized by different levels of metal contamination (S6-S1, this latter being the most contaminated soil). The organisms were analyzed for metal bioaccumulation and for biological parameters as biomarkers of stress (lysosomal membrane stability; lipofuscin lysosomal content; lysosomal/cytoplasmic volume ratio) and genotoxicity (Micronucleus frequency). Chemical analysis showed the loads of Pb, Cd, Zn, and Cu in the worms following exposure. Among the stress biomarkers, lysosomal membrane stability was significantly affected in the coelomocytes of the earthworms exposed already 7 days to different contaminated soils. Organisms exposed for 14 days to S1 showed in the cells of the chloragogenous tissue, a particularly relevant increase in lipofuscin, a biomarker of oxidative stress, and an increase in the lysosome/cytoplasm volume ratio, indicating stressful condition at the tissue level. Moreover, in the same conditions, a decrease in total body weight was observed. At the longer exposure time, the coelomocytes of worms exposed to S1, S2, and S3 (soils with higher metal concentrations) showed a significant increase in micronuclei (MNi) frequency. Expressions of the P21 and topoisomerase genes, which are involved in DNA repair, showed significant up-regulation in the cells of worms exposed to S1, S2, S3, S4 and to a less extend S6. This may indicate that the worms were only able to successfully reduce the level of DNA damage in S4 and S5 if considering MN frequency data. The biomarker data was integrated by the Earthworm Expert System, allowing an objective interpretation of the complex biological data and clearly defining the areas in which the presence of chemicals is toxic for the edaphic organisms. Highlights: Cytotoxic, genotoxic, and transcriptomic responses were evaluated in Eisenia andrei exposed to a polymetallic gradient. Alterations at the cellular and/or tissue levels occur in earthworms exposed to the heavy metal gradient. The genotoxic effects were observed in worms exposed to the highly contaminated soil. Genes related to DNA repair are involved in the molecular response to metal toxicity. Abstract : Polymetallic contaminated soils induced cytotoxicity and DNA alteration in earthworms.